The Analysis of Liquefaction Potential Based on A Comparation of Various Cyclic Resistance Ratio - Tri Wahyu Kuningsih; Rini Kusumawardani (International Conference on Coastal and Delta Areas, 2017)
Prambanan Temple located in the Special Region of Yogyakarta is one of the most beautiful temples in the world. One of the potential geo hazards in the region of Prambanan is the earthquake. Geotechnically, the condition of the soil layer in Prambanan Temple consists of fine and uniform sand. Therefore, there is a possibility of liquefaction, if it receives the earthquake load. This study was aimed to investigate the condition of the subgrade of the Prambanan Temple foundation against the potential of liquefaction. Analysis of liquefaction potential in Regions Prambanan was conducted using semi-empirical method which were the cyclic stress ratio and cyclic resistance ratio with data from the field test results, Standard Penetration Test. The calculation of the value of peak ground acceleration was conducted using various empirical formula. The parameters of the liquefaction threat were based on Liquefaction Potential Index, Liquefaction Risk Index and Liquefaction Severity Index. The analysis showed that the peak ground acceleration value based on the 2006 Yogyakarta earthquake with a magnitude of 6.3 was 0,216g. Based on the condition of existing Prambanan temple with ground water level at -12 meters depth was safe against liquefaction threat. In case of an earthquake with greater strength than the 2006 Yogyakarta earthquake, with a PGA of 0.3 to 0.4g and shallow water level (-1 meters), then liquefaction might potentially occur. Keywords: Liquefaction, Cyclic Stress Ratio, Cyclic Resistance Ratio, Peak Ground Acceleration, Prambanan Temple